Bronze Age sea salt production in Northwestern Iberia - Bettencourt, Ana M. S. (2019)
The neo-glaciation, characterized by a cooling and a decrease in humidity, despite the existence of several episodes of slight climatic improvement, which occurred between the middle of the 4th and the end of the 2nd millennia BCE in the Iberian Northwest, is a well-known reality. The effects of this climate change on the Atlantic coast are also known. It was found that the coastline would be more to the west and irregular than it currently is, with numerous lagoons and different types of wetlands favourable to salt extraction. In this region the earliest evidences of sea salt exploitation are the removable sinks, excavated in slabs of schist. One of these was discovered in a camp-size found at Praia de Carreço in Viana do Castelo, dated by the thermoluminescence of the end of the 3rd, beginning of the 2nd millennium BCE, a period that, in regional terms, is considered from the end of the Chalcolithic to the Early Bronze Age. Due to the geographic distribution of this type of sinks in the north coast, the exploitation of salt during the Bronze Age would have been a relevant activity. Other archaeological evidence of sea salt exploration during the first half of the 2nd millennium BCE comes from the Areias Altas site in Oporto. At this locus, remains of poorly preserved, fragile and fragmented ceramic vessels have been found morphologically similar to those found in other prehistoric salt extraction contexts in western and eastern Europe (Fig. 1). These are containers used for the evaporation of salt water through the brine process, or as moulds for salt. On the northwest coast, in areas with an abundance of granite outcrops or other rocks other than shale, there are also innumerable rock sinks. These were performed by percussion, probably with stone hammers, and polished with rolled pebbles. Some of them are currently on the coastline. By their manufacturing conditions they can also begging in the Bronze Age. In the rare excavations carried out in its environs, still unpublished, they were find network weights, on rolled pebbles, whose chronology dates back at least to the 2nd millennium BCE, in moments of the Middle Bronze Age. Extraction of sea salt may explain, at least in part, the intensity of settlement during the Bronze Age at the edge of the shoreline.